Recording of HIV diagnosis in mental health records: A data linkage cohort study - Margaret Heslin; Olivia Hunt; Emma Tassie; Amelia Jewell; Helena King; Elana Covshoff; Lucy Campbell; Sara Croxford; Rudiger Pittrof; Ann Sullivan; Julie Williams; Michael Newson; et al. (PLoS ONE, 2025)
Background Mental health professionals play a crucial role in promoting the physical well-being of people with mental illness. Awareness of HIV status can enable professionals in mental health services to provide more comprehensive care. However, it remains uncertain whether mental health professionals consistently document HIV status in mental health records. Aims To investigate the extent to which mental health professionals document previously established HIV diagnoses of people with mental illness in mental health records, and to identify the clinical and demographic factors associated with documentation or lack thereof. Methods A retrospective cohort study was conducted using an established data linkage between routinely collected clinical data from secondary mental health services in South London, UK, and national HIV surveillance data from the UK Health Security Agency. Individuals with an HIV diagnosis prior to their last mental health service contact were included. Documented HIV diagnosis in mental health records was assessed. Results Among the 4,032 individuals identified as living with HIV, 1,281 (31.8%) did not have their diagnosis recorded in their mental health records. Factors associated with the absence of an HIV diagnosis included being of Asian ethnicity, having certain primary mental health diagnoses including schizophrenia, being older, being with a mental health service for longer, having more clinical mental health appointments, and living in a less deprived area. Conclusions A significant number of individuals living with HIV who are receiving mental healthcare in secondary mental health services did not have their HIV diagnosis documented in their mental health records. Addressing this gap could allow mental healthcare providers to support those living with HIV and severe mental illness to manage the complexity of comorbidities and psychosocial impacts of HIV. Mental health services should explore strategies to increase dialogue around HIV in mental health settings.